Cervical Artery Dissection in Young Women: Risk of Recurrence During Subsequent Pregnancies. Issue 6 (December 2021) - Assif, Myriam; Lamy, Catherine; De Gaalon, Solène; Caroit, Yolande; Bourcier, Romain; Preterre, Cécile; Guillon, Benoit
Abstract : Objectives: To assess the risk of recurrence of cervical artery dissection (CAD) during pregnancy and puerperium in women with a history of CAD and then help physicians with providing medical information to women who wish to become pregnant. Methods: Women aged 16–45 years who were admitted to our center for a CAD between 2005 and 2017 were identified from the hospital database, and those with spontaneous and symptomatic CAD were included. They were then contacted to answer a questionnaire that was specifically designed in regard to the recurrence of CAD and pregnancies after the primary CAD. Results: Ninety-one patients satisfied our inclusion criteria, and 89 were included in the analysis. During a median follow-up of 7.0 years, 4 women (4.4%) had recurrent CAD, although none during pregnancy or puerperium. Eighteen women (20%) had a total of 20 full-term pregnancies, occurring at least 6 months after CAD. Of these 20 pregnancies, 13 (65%) were vaginal deliveries, and 7 (35%) were cesarean sections. The reason for the absence of pregnancies after the initial CAD was unrelated to the vascular event in 89% of cases, but 8% of the women had been advised by a physician to avoid any future pregnancy or they had been recommended to undergo abortion or sterilization. Conclusion: In this study, there were no CAD recurrences during subsequent pregnancies or postpartum, irrespective of the type of delivery. Thus, pregnancy after a history of CAD appears to be safe.